Managing practicum program in the digital era: A case study of Universiti Utara Malaysia - Hassan, Shahizan; Shiratuddin, Norshuhada (2004)
The purpose of this paper is to share the experience of the Center for Industrial Placement (CIP), Universiti Utara Malaysia (UUM) in managing practicum program since early 1990s. Special focus is made on the use of information technology in assisting the whole CIP's administration. In particular, the discussion addresses some questions, which are what are the current major activities supported and unsupported by information technology and how these supported technologies can be enhanced in term of their features and functions. In order to suggest possible improvements, discussion among management team and an analyst programmer and think-aloud usability testing were conducted with all key personnel in the department.